2008
DOI: 10.1016/j.ydbio.2007.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Activin signals via SMAD2/3 between germ and somatic cells in the human fetal ovary and regulates kit ligand expression

Abstract: Ovarian germ cell survival is dependent upon the formation of primordial follicles, which occurs during fetal life in the human. Activin contributes to germ cell proliferation and survival at this time. SMADs2 and 3 are central elements in the activin signalling pathway and thus indicate sites of activin action. We have investigated the expression and localisation of SMADs2 and 3 in the fetal ovary between 14 and 20 weeks gestation, i.e. preceding and during primordial follicle formation. SMAD3 mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 70 publications
2
71
0
Order By: Relevance
“…56,57 ActA and TGFb have a role on pre-or post-migrated PGC proliferation and survival, and this is mainly mediated by the SMAD2/ SMAD3 signaling pathway. 30 However, it is not clear if ActA has a role in PGC formation during early embryo development. In the current study, we found that ActA has prominent effects on the PGCLCs formation during induction of SDSCs in vitro both in EBLC differentiation and co-culture stages with MEF cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56,57 ActA and TGFb have a role on pre-or post-migrated PGC proliferation and survival, and this is mainly mediated by the SMAD2/ SMAD3 signaling pathway. 30 However, it is not clear if ActA has a role in PGC formation during early embryo development. In the current study, we found that ActA has prominent effects on the PGCLCs formation during induction of SDSCs in vitro both in EBLC differentiation and co-culture stages with MEF cells.…”
Section: Discussionmentioning
confidence: 99%
“…30 ActA also contributes to germ cell proliferation and survival during the formation of primordial follicles. [31][32] In addition, ActA plays an important role in mouse oocyte maturation by promoting the meiosis in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…A network of interacting oocyte transcription factors crucial for oocyte survival and development around the time of follicle formation has been described in the mouse using knockout models (Dong et al 1996, Rajkovic et al 2004, Pangas et al 2006, with some, such as FIGLA, demonstrated to have comparable expression in the human ovary (Huntriss et al 2002. Limited functional studies of human fetal ovaries have identified activin A (Martins da , Coutts et al 2008) and neurotrophin pathways , Spears et al 2003, Childs et al 2010a as likely key determinants of oogonial survival and proliferation and follicle formation (Fig. 2).…”
Section: Establishing the Primordial Follicle Reservementioning
confidence: 99%
“…Activin bA is expressed by germ cells in nests and in vitro exposure to activin A promotes germ cell survival (Martins da . Activin bA expression is lost immediately prior to nest breakdown and follicle formation (Coutts et al 2008), and it is thought that this might act as a switch allowing follicle formation involving the de-repression of kit ligand expression ). In the mouse, activin A administration in utero increased primordial follicle number after birth, although this difference was lost later in life (Bristol-Gould et al 2006a).…”
Section: Establishing the Primordial Follicle Reservementioning
confidence: 99%
“…Activin and TGFB receptors are expressed on both germ cells and somatic cells of the ovary (Findlay et al 2002, Kaivo-oja et al 2006, whereas the active phosphorylated SMADS 2 and 3, which activin signals through, are present only in somatic cells. Thus, foetal somatic cells are targets of activin action (Coutts et al 2008). Low levels of inhibin a and activin bA mRNA and protein were also detected in the stromal and granulosa cells of ovaries of foetal mice at 13.0 dpc (Weng et al 2006).…”
Section: Inhibins and Activinsmentioning
confidence: 97%